Molecular epidemiology of pachyonychia congenita in the Israeli population. (1st June 2021) - Pavlovsky, M.; Peled, A.; Samuelov, L.; Malki, L.; Malovitski, K.; Assaf, S.; Mohamad, J.; Meijers, O.; Eskin‐Schwartz, M.; Sarig, O.; Sprecher, E.
Summary: Background: Pachyonychia congenita (PC) is a rare autosomal dominant disorder featuring palmoplantar keratoderma, nail dystrophy, oral leucokeratosis, pilosebaceous cysts and natal teeth. PC results from dominant mutations in one of five genes ( KRT6A, KRT6B, KRT6C, KRT16, KRT17 ) encoding keratin proteins. Aim: To delineate the clinical and genetic features of PC in a series of Israeli patients. Methods: We used direct sequencing of genomic DNA, and also used cDNA sequencing where applicable. Results: We collected clinical information and molecular data in a cohort of Israeli families diagnosed with PC ( n = 16). Most of the patients were Ashkenazi Jews and had a family history of PC. The most common clinical findings were painful focal plantar keratoderma (94%) accompanied by nail dystrophy (81%), pilosebaceous cysts (31%) and prenatal/natal teeth (13%). In contrast to the high prevalence of KRT6A mutations in other populations, we found that KRT16 mutations were the most common type among Israeli patients with PC (56%). Most (77%) of the Israeli patients with PC with KRT16 mutation carried the same variant (c.380G>A; p.R127H) and shared the same haplotype around the KRT16 locus, suggestive of a founder effect. Conclusion: The data gleaned from this study emphasizes the importance of population‐specific tailored diagnostic strategies.